EFEKTIFITAS COMPUTER AIDED LEARNING (CAL) DALAM PEMBELAJARAN KOSAKATA BAHASA INGGRIS SISWA SEKOLAH DASAR - Wulandari, Dewi Ayu Nur (LPPM Universitas Nusa Mandiri, 2012)
Advances in technology encourage the use of technology in teaching and learning process. The use of technology in the learning process is rapidly gaining popularity along with the development of information technology which is a supporting factor in the development of education and also to provide innovative solutions to the problems faced. Computer Aided Learning (CAL) is a method of approach to teaching and learning activities with the help of computer technology as an auxiliary medium is used to help learners understand the subject matter ranging from displays and provide reinforcement material also as a tool to assess learning achievement in which the material is packaged in the form software (software). Besides using CAL to learners will be able to interact with the interactive learning program that is available so they can learn to follow the ability of each learner and can also repeat a topic they have not understood the lessons step by step. By using CAL, students become more independent in learning, because the learning process not only depends on the teacher.